Ukraine : Staff Report for the 2012 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
Following the 2008/9 financial crisis and deep recession, a cyclical recovery took hold in Ukraine, supported by a stronger external environment. Efforts to consolidate public finances and repair the banking system began strengthening Ukraine's resilience to external shocks. More recently, policies have not been sufficient to meet key objectives, and the government has hesitated to undertake politically unpopular reforms. The external environment has become less supportive, and the recovery is losing momentum.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet